Cycling Through the Pandemic Tactical Urbanism and the Implementation of Pop-Up Bike Lanes in the Time of COVID-19 - Ortar, Nathalie; Rérat, Patrick (The Urban Book Series,, 2024)
This open access book provides insight on how the tactical urbanism has the capacity to influence change in mobility practices such as cycling. COVID-19 crisis prompted the public authorities to rethink the use of public space in order to develop means of transport that are both efficient and adapted to the health context and their effects on cycling practices in Europe, North, and South America. Its contributors collectively reveal and evidence through policies analysis, mapping, and innovative qualitative analysis bridging video and interviews, how those new infrastructures and policies can be a trigger for change in a context of mobility transition. This book provides an important element on the way local authorities can act in a quicker and more agile way. While some decisions are specific to the context of the beginning of the pandemic, the analysis offers lessons on the way to implement the transition toward a low-carbon mobility, on the importance of processes based on trials and errors, on the political stakes of reallocating road space.